Effects of CdS quantum dot in polymer nanocomposites: In terms of luminescence, optic, and thermal results - Keskin, Ilker Cetin; Türemiş, Murat; Kati, Mehmet Ismail; Kibar, Rana; Cetin, Ahmet (Pergamon-Elsevier Science Ltd, 2019)
CdS quantum dots (QDs) which have unique luminescence efficiency were synthesized by two-phase method using oleic acid (OA) as a surfactant. The nanocomposites have been obtained by blended CdS quantum dots with low-density polyethylene (LDPE) in different ratios. Primarily, radioluminescence (RL) properties were investigated as well as their structural (FT-IR, XRD), morphological (TEM, SEM), thermal (TG-DTA) and absorption (UV-Vis) properties of these nanocomposites. The RL peaks of OA-capped CdS QD were observed at 456 nm and 655 nm. As a consequence of the nanocomposites being doped with powder CdS QD, a significant blue shift was observed in the absorption bands. The optical band gap of CdS was calculated as- 2.3 eV. The nanocomposites blended with CdS QD, this value increased to- 2.7 eV. It has also been observed that nano particles cause nanocomposites to have lower melting temperatures.
Keywords: Quantum dots; Radloluminescence (RL); Low-Density Polyethylene (LDPE); Optical absorption; Structural characterization; Thermal analysis